New moon - Meyer, Stephenie (London, United Kingdom : Little, Brown and Company, 2006)
When the Cullens, including her beloved Edward, leave Forks rather than risk revealing that they are vampires, it is almost too much for eighteen-year-old Bella to bear, but she finds solace in her friend Jacob until he is drawn into a "cult" and changes in terrible ways.
1. Party -- 2. Stitches -- 3. The end -- 4. Waking up -- 5. Cheater -- 6. Friends -- 7. Repetition -- 8. Adrenaline -- 9. Third wheel -- 10. The meadow -- 11. Cult -- 12. Intruder -- 13. Killer -- 14. Family -- 15. Pressure -- 16. Paris -- 17. Visitor -- 18. The funeral -- 19. Race -- 20. Volterra -- 21. Verdict -- 22. Flight -- 23. The truth -- 24. Vote.
Keywords: FANTASY -- FICTION